From Indentured Servants to Slaves, Daily-life Conditions and the Ecomic Factors Behind this shift:study case verginia colony - Mansour ,Ismail; Hebal ,Abdelaziz; Khalfa, Sayeh (Faculty of Letters and Foreign Languages Department of English, 2017)
This is an inquiry of the institution of indentured servitude and slavery in the British Colony of Virginia. This study investigates the innovation of indentured servitude and describes their daily-life conditions. It provides an analysis of how the indentured servitude became a central institution in the economy and society of Virginia colony. It also investigates servitude in law providing examples of treatment and resistance of servants. This study provides an economic analysis of the decline of indentured servants and the rise of new system of labor, slavery. However, It traces the origin of the Atlantic slavery, and the first existence of slaves in Virginia. It eventually portrays their conditions and religious faith